Should a repeat cervical cerclage be inserted when the primary cerclage fails, to prevent pregnancy loss and preterm birth? A systematic review and meta-analysis - Alexandra Emms; Matthew Vaughan; Rebecca Man; R. Katie Morris; Victoria Hodgetts-Morton; Nicole Pilarksi (PLoS ONE, 2025)
Introduction Spontaneous preterm birth (sPTB) occurs in 0.5–1% of pregnant women and is commonly attributed to cervical insufficiency. Cervical cerclage can reduce the rate of spontaneous preterm birth in high-risk women with a shortened cervix. Management options when primary cerclage fails are uncertain. This review aims to synthesise the evidence for repeat cervical cerclage in the same pregnancy following primary cerclage failure, to understand outcomes and aid decision making for patients and clinicians. Materials and methods Databases were searched according to a prospective protocol registered with PROSPERO (CRD42025638147). Included studies reported outcomes for pregnant women with a cervical cerclage in situ that failed and compared repeat cervical cerclage with expectant management. The primary outcome was a composite outcome of pregnancy loss; to include miscarriage, stillbirth, neonatal death and termination of pregnancy. Secondary outcomes included preterm birth less than 37 and less than 34 weeks, miscarriage and previable neonatal death less than 24 weeks, birthweight and gestational age at delivery. Random effects meta-analysis was performed using Review Manager software (RevMan) and risk of bias was assessed using the Robins-I tool. Results Database and citation searching retrieved 1006 titles and abstracts. There were 20 papers that underwent full text review. Six retrospective cohort studies met inclusion criteria for meta-analysis. There was no significant difference in pregnancy loss (odds ratio (OR) 1.65, 95% confidence interval (CI) 0.23–11.62), preterm birth less than 34 weeks (OR 1.11 95% CI 0.14–8.70) or preterm birth less than 37 weeks (OR 1.88 95% CI 0.74–4.80) for repeat cervical cerclage compared to expectant management, with a trend towards improved outcomes with expectant management. Conclusions There was no evidence of any difference in pregnancy loss or preterm birth with or without repeat cervical cerclage. The overall quality and quantity of evidence is poor and patients should be informed of this. Further research in this area is required for informed decision making.